EFEKTIVITAS PENERAPAN TRANSPARANSI HARGA PELAYANAN RUMAH SAKIT DALAM MEMBERIKAN SINYAL INFORMASI KEPADA PASIEN DAN RUMAH SAKIT - Lumbanraja, Lissa MJR; Sjaaf, Amal Chalik (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The transparency of hospital service prices means that information about the prices of medical services and procedures offered by hospitals is openly available and easily accessible to the general public. Patients can compare the fees charged by different hospitals for the same medical service. This can encourage competition between hospitals to offer more competitive prices. Price transparency is still complex in many healthcare systems, and there are challenges that need to be addressed in implementing price transparency that is effective and beneficial for patients. This research is a research based on Literature Review with a research approach based on the analysis of scientific articles and theses with study methods, structured evaluation, classification and categorization of evidence-based that has existed or been produced before, which has been discussed and published in the health sector. Focus is set for publication from 2013 to 2023. The data used are secondary data, obtained from the results of research that has been done. The hope is that with price transparency, patients can evaluate their healthcare options, compare prices from all providers, and make decisions that align with their own financial circumstances and preferences. However, based on the results of research and discussion described above, it can be concluded that there is no significant impact on the selection and decision of patients to choose hospital services with price information from service providers.